HUBUNGAN ANTARA MOTIVASI BERPRESTASI DENGAN DISIPLIN KERJA GURU TAMAN KANAK - KANAK SE-KECAMATAN RAMBAH KABUPATEN ROKAN HULU - indarto, Wusono; ', Mardiah; ', Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Mardiah. The relationship between achievement motivation and discipline Kindergarten teacher Rambah Rokan Hulu. The purpose of this study was to determine whether there is a correlation between achievement motivation and discipline teachers of kindergarten throughout the district Rambah Rokan Hulu. This research is a correlation study, variables consist of two variables: the variable motivation and work discipline variables. The population of all kindergarten teachers Rambah Rokan Hulu district that is about 40 people. Based on research results using statistical analysis has a positive and significant relationship between achievement motivation and discipline Kindergarten teacher Rambah Rokan Hulu. It can be seen from the assessment of the acquisition value test "t", the result count of 6,412, while the t (5%) (df = n-2 = 40-2 = 38) up to 2,000 t. Because the count is greater than t or 6,412> 2,000, it means that there is a positive and significant relationship between achievement motivation and discipline.Keywords: Achievement Motivation, Work Discipline